β-Thalassemia Intermedia Caused by the β-Globin Gene 3′ Untranslated Region: Another Case Report - Jiang, Fan; Chen, Gui-Lan; Li, Jian; Tang, Xue-Wei; Li, Dong-Zhi (Hemoglobin, 2022)
The 3' untranslated region (3'UTR) is associated with mRNA stability because of its involvement in 3' end processing, polyadenylation, and mRNA capping. Mutations located in this area can cause a phenotype compatible with β+-thalassemia (β+-thal). We report a Chinese subject with β-thal intermedia (β-TI) who developed transfusion-dependent anemia. Molecular studies revealed that the patient was a compound heterozygote for two β-thal alleles: codons 41/42 (-TTCT) (HBB: c.126_129delCTTT) and term codon +32 (A>C) (HBB: c.*32A>C).The 3' untranslated region (3'UTR) is associated with mRNA stability because of its involvement in 3' end processing, polyadenylation, and mRNA capping. Mutations located in this area can cause a phenotype compatible with β+-thalassemia (β+-thal). We report a Chinese subject with β-thal intermedia (β-TI) who developed transfusion-dependent anemia. Molecular studies revealed that the patient was a compound heterozygote for two β-thal alleles: codons 41/42 (-TTCT) (HBB: c.126_129delCTTT) and term codon +32 (A>C) (HBB: c.*32A>C).